Language policy and language learning in Macedonia. Which lessons may be adopted from the Swiss model? - Xhaferri, Gëzim (Linguistik Online, 2014)
This paper also investigates Switzerland's multilingual and multicultural society, which serves as a successful and positive example of how a nation can deal with a multilingual population and the integration of its population. With this in mind, the question is raised here whether the model of Switzerland's language policy and national language instruction can perhaps also serve as an example for the Republic of Macedonia.